2022
DOI: 10.1155/2022/3102743
|View full text |Cite
|
Sign up to set email alerts
|

Constructing and Validating a Pyroptosis-Related Genes Prognostic Signature for Stomach Adenocarcinoma and Immune Infiltration: Potential Biomarkers for Predicting the Overall Survival

Abstract: Background. Stomach adenocarcinoma (STAD) is a kind of cancer that begins in the stomach cells and has a poor overall survival rate. Following resection surgery, chemotherapy has been suggested as a curative method for stomach cancer. However, it is ineffective. Pyroptosis, a kind of inflammatory programmed cell death, has been shown to play a significant role in the development and progression of STAD. However, whether pyroptosis-related genes (PRGs) can be utilized to predict the diagnosis and prognosis of g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 41 publications
(39 reference statements)
1
3
0
Order By: Relevance
“…IL-1β induces cell death by forming pores in the cell membrane through caspase-1, 4, 5 and 11. The NLRP3 inflammasome has been identified as a key component in the initiation of pyroptosis [39,40]. Our findings demonstrate that the upregulation of PFKFB3 reduces pyroptosis in GC cells.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…IL-1β induces cell death by forming pores in the cell membrane through caspase-1, 4, 5 and 11. The NLRP3 inflammasome has been identified as a key component in the initiation of pyroptosis [39,40]. Our findings demonstrate that the upregulation of PFKFB3 reduces pyroptosis in GC cells.…”
Section: Discussionsupporting
confidence: 57%
“…Research has found that when cells are stimulated by pathogenic and damage-related molecular patterns, inflammatory caspase-1 activation is induced, leading to the shear formation of GSDMD-C and cytotoxic GSDMD-N, the executors of cell pyroptosis. The latter is recruited to form cell pyroptosis pores, promoting the maturation of IL-1 β release of IL-18 into the extracellular space, inducing an inflammatory cascade reaction [39,40]. Pyroptosis is initiated by endogenous danger signals or metabolites, leading to the production of IL-1β.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, RGS1 , another component of the PRS calculation, was found to be a novel marker of CD8 + T cell depletion, leading to sustained antigenic stimulation and T-cell depletion, according to single-cell transcriptome analysis by Bai et al 36 . RGS is also a member of the pyroptosis-related gene model proposed by Xu et al , thereby implying its pivotal role in the process of pyroptosis 37 . Additionally, we observed that the association between the PRS and macrophage polarization was limited to the tumor center, possibly because of the presence of VCAN , a constituent molecule of the PRS.…”
Section: Discussionmentioning
confidence: 99%
“…Most importantly, the high expression of LncRNA ADAMTS9-AS2 also sensitizes gastric cancer cells that originally showed resistance to cisplatin [32] . Studies have shown that overexpression of lncRNA ADAMTS9-AS2 inhibits gastric cancer development by regulating the miR-223-3p/NLRP3 axis-mediated pyroptosis process [33,34] . In addition, Icariin (ICA), which is mainly found in Epimedium, has multiple biological activities, and the anticancer effects of ICA are associated with the signaling axis between hsa_circ_0003159, miR-223-3p, and NLRP3.…”
Section: Stomach Cancermentioning
confidence: 99%